2019
DOI: 10.1136/bjsports-2018-100310
|View full text |Cite
|
Sign up to set email alerts
|

How should clinicians rehabilitate patients after ACL reconstruction? A systematic review of clinical practice guidelines (CPGs) with a focus on quality appraisal (AGREE II)

Abstract: ObjectivesTo summarise recommendations and appraise the quality of international clinical practice guidelines (CPGs) for rehabilitation after ACL reconstruction.DesignSystematic review of CPGs (PROSPERO number: CRD42017020407).Data sourcesPubmed, EMBASE, Cochrane, SPORTDiscus, PEDro and grey literature databases were searched up to 30 September 2018.Eligibility criteriaEnglish-language CPGs on rehabilitation following ACL reconstruction that used systematic search of evidence to formulate recommendations.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
129
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(140 citation statements)
references
References 52 publications
5
129
0
6
Order By: Relevance
“…However, although it is important to include OKC knee extension exercise in the restoration of quadriceps strength after ACLR, recommendations regarding the timing of implementation of OKC strengthening is not currently consistent in clinical practice guidelines. 29 Previous studies have reported a significant decrease in quadriceps strength of the uninvolved limb over time after ACLR when compared with presurgical level, 14,15,30-32 but we are unaware of evidence showing a decrease in hamstring strength of the uninvolved limb over time after ACLR. These studies suggest that patients need a focus on bilateral strengthening following surgery.…”
Section: Discussionmentioning
confidence: 78%
“…However, although it is important to include OKC knee extension exercise in the restoration of quadriceps strength after ACLR, recommendations regarding the timing of implementation of OKC strengthening is not currently consistent in clinical practice guidelines. 29 Previous studies have reported a significant decrease in quadriceps strength of the uninvolved limb over time after ACLR when compared with presurgical level, 14,15,30-32 but we are unaware of evidence showing a decrease in hamstring strength of the uninvolved limb over time after ACLR. These studies suggest that patients need a focus on bilateral strengthening following surgery.…”
Section: Discussionmentioning
confidence: 78%
“…In conclusion, the present preliminary results indicate that, for ACL reconstructed subjects involved in the early post-surgery rehabilitation, the adoption of the new functional brace with continuous leg-applied resistance to knee flexion allows a greater recovery of injured knee kinematics and better management of sagittal ground reaction force during gait, particularly at weight acceptance, compared to traditional knee brace locked in full extension. To date, the medical choice on whether to use a post-operative brace is up to the surgeons' discretion due to its non-significant additional benefit on the knee function and stability in the short term when added to standard therapy [9][10][11]. However, preliminary findings from this study suggest that the adoption of the new functional knee brace could be considered as a viable alternative to traditional brace for a better recovery of the gait biomechanics, reducing the risk of joint damaging while adding an intrinsic rehabilitation with the persistent applied resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Early post-surgical ACL rehabilitation (0-6 weeks post-surgery) usually involves the loading and mobilization of the injured limb as well as the adoption of orthopedic braces. Despite its large adoption following ACL reconstruction [8], evidence from systematic reviews and meta-analysis indicates that traditional bracing adds no significant benefit in the short term on the clinical outcomes of function and stability when added to standard therapy [9][10][11]. Consequently, the adoption or not of a post-operative brace remains a subject of debate.…”
Section: Introductionmentioning
confidence: 99%
“…El resto de estudios comienzan a partir de las dos semanas posintervención. Si se tiene en cuenta la revisión de Andrade et al (2019), en la cual compara y analiza las guías clínicas más actuales sobre la rehabilitación del LCA, pone de manifiesto la necesidad de realizar en la primera semana postoperatoria los siguientes aspectos: movilización inmediata de la rodilla; entrenamiento neuromuscular y de fuerza; ejercicios precoces en carga completa; crioterapia; EENM de acuerdo con las circunstancias individuales; y finalmente, se desaconseja la utilización de movilizaciones pasivas y el uso de rodilleras funcionales (Andrade, Pereira, Van Cingel, Staal, y Espregueira-Mendes, 2019).…”
Section: Discussionunclassified